Synthesis and characteristic (analisys) of hydrogel bandage of biomedical purpose - Alpysbayeva, B.E.; Rakhmetullaeva, R.K.; Ishchanova, A.K.; Beksultanov, Zh.I.; Mun, G.A. (Recent Contributions to Physics, 2012)
This paper presents the results obtained in the study of nanostructured hydrophilic polymer obtained by chemical methods. Structure and properties of hydrogels modified with silver nanoparticles were investigated using optical and scanning probe microscopy.